Causal Relationship Model of Water Conservation Behavior - Udonboon, Chalermsak; Thiengkamol, Nongnapas; Thiengkamol, Chatchai (Mediterranean Journal of Social Sciences, 2012)
The populations were 18,463 upper secondary school students from school under Secondary Service Area Office 24 (Kalasin), Northeastern region of Thailand in academic year of 2012. The with Multi-stage random sampling technique was employed to collect the sample for 400 upper secondary school students. The research instrument was the questionnaire and it was used for data collecting. LISREL was used for model verification. The objective of this study was to develop a causal relationship model of water conservation behavior of upper secondary school student. Considering on structural model confirmatory factors of Psychological Trait (PsT), Psychological State (PsS), Environmental Knowledge (EK) and Environmental Education (EE) were able to explain the variation of endogenous factors of Inspiration of Public Consciousness (INS) to caused Water Conservation Behaviors (BEH) with 60.00 percents. As a result, the equation 1 can be written as following. BEH = 0.96*INS + 0.28*EK + 0.052*PsS - 0.14*PsT - 0.11*EE ……….…(1) R2 = 0.60 Equation (1) factors that had the most effect to Water Conservation Behaviors (BEH) was Inspiration of Public Consciousness (INS) and subsequences were Environmental Knowledge (EK) and Psychological State (PsS) but Psychological Trait (PsT) and Environmental Education (EE) with negative direction, these were able to explained the variation of Water Conservation Behaviors (BEH)with 60.00 percents. Moreover, confirmatory factors of Psychological Trait (PsT), Psychological State (PsS), Environmental Knowledge (EK) and Environmental Education (EE) were able to explain the variation of confirmatory factors of Inspiration of Public Consciousness (INS with 86.00 percents. Therefore, the equation can be written as following equation 2. INS = 0.79*EE +0.25*PsT - 0.21*PsS - 0.17*EK ……………………….(2) R2 = 0.86 Equation (2) factors that had the most effect to Inspiration of Public Consciousness (INS) was Environmental Education (EE) and subsequences were Psychological Trait (PsT) but Psychological State (PsS) and Environmental Knowledge (EK) with negative direction, these were able to explained the variation of Inspiration of Public Consciousness (INS) with 86.00 percents